Report on the diagnosis and treatment of 3 cases of emphysematous pyelonephritis with two different outcomes - Zhang, Minna; Luo, Hongxing; Tan, Su; Fei, Tao; Tang, Zhimin; Li, Qiang; Lin, Haixing (Frontiers in Medicine, 2024)
Background: Emphysematous pyelonephritis (EPN) is a rare acute severe necrotising infection of the kidneys in clinical practice. It is characterized by the presence of gas in the renal parenchyma, collecting system, or perirenal tissue. The prognosis is poor, with a high nephrectomy rate and a mortality rate of up to 20-40%.Methods: Retrospective analysis of 3 cases of emphysematous pyelonephritis with two different outcomes.Results: Three patients who we described were all female with diabetes mellitus, and their blood sugar was poorly controlled. One patient with the advanced age and poor general health died due to the patient's family choosing to terminate therapy. Two patients underwent surgical procedures achieved an excellent clinical recovery. Both of them underwent percutaneous nephrostomy and perinephric abscess puncture drainage before nephrectomy. Escherichia coli were the microorganisms implicated. Conclusion: EPN is a rare and severe urinary system infection. Computed tomography (CT) and microbiological culture confirmed the diagnosis. Control of diabetes, sensitive antibiotic therapy, fluid resuscitation and prompt surgical intervention are crucial.